Relationship Between Eating Behaviors and Physical Activity Among Primary and Secondary School Students: Results of a Cross‐Sectional Study. (23rd July 2013) - Morin, Pascale; Turcotte, Sylvain; Perreault, Gino
ABSTRACT: BACKGROUND: With a view toward developing concerted efforts in fostering healthy eating habits and a physically active lifestyle among young people, a study was carried out to explore associations between eating behavior and physical activity (PA). METHODS: In the school district, questionnaires were completed at home by parents of primary school children (N = 8612) and by secondary school youth (N = 5250) during a break in the schedule. The rates of response were 79% and 83%, respectively. Inferential and descriptive analyses were performed. RESULTS: The results indicate significant differences between the eating behaviors of young people who engage in 60 minutes of daily PA and those who are sedentary. The physically active children were generally more likely to eat fruit, vegetables, and whole‐grain products and to have breakfast (p < .05 among high‐school students). The lack of self‐confidence (55%) and not enjoying PA (46%) stood out as the greatest obstacles facing adolescents trying to lose weight. CONCLUSION: There should be particular actions targeting students in the last half of primary school aimed at developing individual accountability and autonomy with respect to healthy eating and PA. These actions should also consider sex differences and those who have more sedentary lifestyles.